ANALISIS PENERAPAN PENGETAHUAN AKUNTANSI DALAM PENCATATAN TRANSAKSI DIKEHIDUPAN SEHARI-HARI PADA MAHASISWA PERANTAU - Arismon Rusjaya Meliala; Herkulana Herkulana; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe study aims to know the practical application of accounting knowledge in dayto-day transaction natation to oconomic education student FKIP Untan (Reg.A). the reearch approach used in this study is a qualitative approach the method used in this study is a descriptive method with a case-study form. The data source in this study is the student activee conomics education that is on the way and is housing and housing the 8 students from 2016, 2017, 2018 and 2019. The data-gathering procedure in this study is to use interviews and documents. The data analysis in this research is using domain analysis. The atypical examination technique in this study is the use of reference materials and check. This study is the level of understanding that student living in a country in which non-commissioned students have common characteristics, students more likely no to apply accounting knowledge into daily life, as indicated by their inttentions and actions, such as not keeping a record of receiving and spending on a day-to-day basis.Key words: Application, Accounting Knowledge, Student messenger